«Հովարդ Կարագյոզյան» հաստատության գործունեությունը հայրենիքում - Վարդանյան, Արարատ (ԱրՊՀ հրատ․)
Фонд “Говард Карагезян” – благотворительная организация. Основана в 1921г. в Нью Йорке Миграном и Забел Карагезянами с целью лечения и воспитания осиротевших армянских детей. С 1992 года действует Армянский центр в Ереване с филиалами в Гюмри (с 1995г.), Горисе и Степанакерте (с 1996г.), Ванадзоре (с 2000г), с помощью которых осуществляются здравоохранительные, социальные, культурно-образовательные и другие благотворительные проекты. The Howard Karagheusian Foundation is a benevolent organization. It was founded by Mihran and Zabel Karagheusian in New York in 1921 with the aim to treat and raise the Armenian orphans. Since 1992 the Armenian Centres function in Yerevan with branches in Gyumri (since 1995), Goris and Stepanakert (since 1996), Vanadzor (since 2000) which fulfill health, social, educational-cultural and other charitable projects.
Keywords: Բարեգործություն